Spatial variation in vegetation productivity trends, fire disturbance, and soil carbon across arctic-boreal permafrost ecosystems. (14th September 2016) - Loranty, Michael M; Lieberman-Cribbin, Wil; Berner, Logan T; Natali, Susan M; Goetz, Scott J; Alexander, Heather D; Kholodov, Alexander L
Abstract: In arctic tundra and boreal forest ecosystems vegetation structural and functional influences on the surface energy balance can strongly influence permafrost soil temperatures. As such, vegetation changes will likely play an important role in permafrost soil carbon dynamics and associated climate feedbacks. Processes that lead to changes in vegetation, such as wildfire or ecosystem responses to rising temperatures, are of critical importance to understanding the impacts of arctic and boreal ecosystems on future climate. Yet these processes vary within and between ecosystems and this variability has not been systematically characterized across the arctic-boreal region. Here we quantify the distribution of vegetation productivity trends, wildfire, and near-surface soil carbon, by vegetation type, across the zones of continuous and discontinuous permafrost. Siberian larch forests contain more than one quarter of permafrost soil carbon in areas of continuous permafrost. We observe pervasive positive trends in vegetation productivity in areas of continuous permafrost, whereas areas underlain by discontinuous permafrost have proportionally less positive productivity trends and an increase in areas exhibiting negative productivity trends. Fire affects a much smaller proportion of the total area and thus a smaller amount of permafrost soil carbon, with the vast majority occurring in deciduous needleleaf forests. Our results indicate that vegetation productivity trends may be linked to permafrost distribution, fire affects a relatively small proportion of permafrost soil carbon, and Siberian larch forests will play a crucial role in the strength of the permafrost carbon climate feedback.